2011
DOI: 10.1155/2011/459839
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant Property of Leaf Extracts ofVitex donianaandMucuna pruriens

Abstract: Oxidative stress and impaired antioxidant system have been implicated in the pathophysiology of diverse disease states. The phytochemical screening and antioxidant property of fresh leaves of Vitex doniana and Mucuna pruriens, used in the management and treatment of various diseases, were studied. The extracts (ethanol and distilled water) were screened for the presence of phytochemicals, and their inhibition of 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical was used to evaluate their free radical scavenging ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 13 publications
7
74
1
2
Order By: Relevance
“…Les phases hexaniques rassemblées ont été évaporées pour constituer la fraction hexanique. (Agbafor et Nwachukwu, 2011 ;Lagnika et al, 2012).…”
Section: Fractionnement Liquide/liquide De L'extrait éThanoliqueunclassified
See 1 more Smart Citation
“…Les phases hexaniques rassemblées ont été évaporées pour constituer la fraction hexanique. (Agbafor et Nwachukwu, 2011 ;Lagnika et al, 2012).…”
Section: Fractionnement Liquide/liquide De L'extrait éThanoliqueunclassified
“…Par ailleurs, dans les travaux menés par Agbafor et Nwachukwu (2011) L'objectif du fractionnement bioguidé consistait à identifier une fraction dont l'activité antioxydante est supérieure à celle de l'extrait éthanolique total. Les feuilles de Vitex doniana contiennent des flavonoïdes, des tanins, des terpénoïdes, des composés phénoliques, des alcaloïdes et les vitamines A, C et E (Suleiman et Yusuf, 2008 ;Muanda, 2010 ;James et al, 2014 (Suleiman et Yusuf, 2008 ;Muanda, 2010 ;Lagnika et al, 2012).…”
Section: Fractionnement Liquide/liquide De L'extrait éThanoliqueunclassified
“…Usually, they include steroids, alkaloids, flavonoids, tannins, terpenoids, and several others [2]. Many phytochemicals possess antioxidative property, which can lessen the danger of many diseases [3]. The prominence of therapeutic plants and the impact of phytomedicine derived from it have a significant influence to the well-being of the considerable world population, which have engrossed awareness from different disciplines of research.…”
Section: Introductionmentioning
confidence: 99%
“…The pod was reported as anthelmintic, while root was used in the treatment of nervous disorders and blood purification. In many countries, this plant is also used in the treatment of cholesterol, diabetes, hypertension, paralysis, rheumatism, cancer, tumors, tuberculosis, asthma, cholera, diarrhea, dysentery, irritation, burns, cough, muscle pain, and many others [5][6][7]. Various studies reported the bioactivity of Mucuna pruriens, such as increasing the sexual activity of normal male rats, hepatoprotective activity with increasing the in vivo antioxidants [8], antidiabetic activity [9][10][11][12], and as a potential antiparkinson from the seeds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the phytochemical study showed that Mucuna pruriens contains saponins, tannins, anthraquinones, steroids, terpenoids, alkaloids, flavonoids, resins, and glycoside-containing compounds [5,[15][16][17]. The seed of Mucuna pruriens is known contains L-DOPA, a precursor to the neurotransmitters dopamine.…”
Section: Introductionmentioning
confidence: 99%